Peningkatan Pelayanan Berbasis Android Di Desa Sukorejo Sebagai Indicator Desa Digital - Sholiha, Hanifatus; Fitriyah Ningsih, Dahliatul; Setiawan, Aris (Humanist Journal, 2023)
A paradigm that is oriented towards public administration has developed by prioritizing public services. This research was conducted to help overcome the obstacles faced by the system for recording and managing population data which still uses a system for recording and managing population data manually. An Android-based service improvement program was carried out in Sukorejo Village. The system is created using tools in the Android Studio and MySQL database which will be interpreted in the Android application. This research method uses the ADDIE (Analysis, Design, Development, Implementation and Evaluation) method. The results of this study show. This application can facilitate village officials in the process of making data collection and making correspondence reports. This application can also make it easier for residents of Sukorejo Village to submit letters. With this application, the correspondence service process becomes faster and more effective.